Influence of pH on the Cytotoxic Activity of Inositol Hexakisphosphate (IP6) in Prostate Cancer - Betton, Blandine; Gannon, Philippe O.; Koumakpayi, Ismaël Hervé; Diallo, Jean-Simon; Mes-Masson, Anne-Marie; Saad, Fred (Frontiers in Oncology, 2011)
Objectives: In the present study, we investigated whether the pH of IP6 could influence its anti-tumoral activity in vitro. Methods: PC-3 cells were exposed to IP6 at pH 5, pH 7, and pH 12 and we evaluated the metabolic activity (WST-1 assay), cell proliferation (cell count), cell cycle distribution (FACS), and mitochondrial depolarization (JC-1 staining) in vitro. Results: Our results demonstrated that IP6 at pH 5 and pH 12 were more potent at lowering the metabolic activity of PC-3 cells than IP6 at pH 7. Treatment with IP6 at pH 12 also caused the greatest inhibition in cellular proliferation and accumulation of PC-3 cells in sub-G1. Finally, IP6 at pH 12 lead to a reduction in phospho-AKT and phospho-PDK1 and upregulated phospho-ERK. Conclusion: Together, our data strongly suggest that the pH of IP6 effectively modulates its anti-tumoral activity and should be reported in future studies.